Draft Ninth Five Year Plan 1997-2002 and Annual Plan 1997-2002 and Annual Plan 1997-98 A Supplement of Volume II Government of Uttar Pradesh - Planning Commission (Planning Commission, 1997)
A1- Schemes completed upto 1995-96 and likely to be completed during 1996-97 (spillover liability if any for 1997-98 and beyond), Development of Rajma pulse in Uttaranchal (Provided Rs. 500/- per Qtl. on Rajma Seed and Rs 150/- in Fertilizer and Rs 100/- on Pesticides per Hectare subsidy is given under this scheme. 1992-93, Subsidy on HYV seed and composite fertilizer demonstration in tribal block of Uttaranchal (To provide 50% subsidy on HYV seeds and Rs 80/- subsidy on per fertilizer demonstration in 16 blocks (1980-81)
Draft Ninth Five Year Plan 1997-2002 and Annual Plan 1997-2002 and Annual Plan 1997-98
Government of Uttar Pradesh